Shocks, child labor and schooling dropouts in Argentina - Cruces, Guillermo Antonio (2011)
This paper studies the relationship between youth labor market experiences and adult labor outcomes, in the short and long term. The analysis is conducted using pseudo-panel data for 8 Latin American countries, a region characterized by high unemployment and informality rates. The main findings indicate marked heterogeneities across countries, with some characterized by short-term blemishes while others by longer lasting effects. These results suggest that youth experiences are relevant to adult‟s working lives, but that the channels driving them are specific to each labor market. Therefore, a detailed description of these findings must place special emphasis on these heterogeneities.